Seyyed Hossein Nasr's Unity Concept: A Study of the Relationship between Science and Islam - Hulawa, Djeprin Ersen; Yasin, Arbi; Alwizar, Alwizar (AL-FIKRA, 2023)
AbstractThis research is motivated by the desire to dig deeper into the content of esotericism in the building of the integration of science and religion (Islam) from the perspective of Seyyed Hossein Nasr (hereinafter referred to as Nasr) because the patterns and models of the integration of science and Islam implemented in various universities today are more exoteric in appearance. stand out on the aspect of identity alone. The formulation of the research problem is how is the concept of integration of science and Islam from the perspective of Nasr. This research method is a literature study by prioritizing documentation techniques as a data collection tool. The researcher tracked various references of literature relevant to the theme of the study and found more than 50 pieces of literature sourced from various journals, books, and other references published at least in the last 10 years. Based on the research results, it is concluded that Nasr with his esoteric concept places the principle of unity (Tawhid) as the pinnacle of integration where science and Islam are closely attached to the same origin traditionKeyword: Unity, integration of science and Islam, Seyyed Hossein Nasr AbstrakPenelitian ini dilatarbelakangi kehendak untuk menggali lebih dalam kandungan esoterisme pada bangunan integrasi sains dan agama (Islam) persepktif Seyyed Hossein Nasr (selanjutnya disebut Nasr), sebab pola dan model integrasi sains dan Islam yang diimplementasikan di berbagai Perguruan Tinggi dewasa ini lebih bersifat eksoteris yang tampak mononjol pada aspek identitasnya saja. Rumusan masalah penelitian ini adalah bagaimana konsep integrasi sains dan Islam perspektif Nasr? Metode penelitian ini adalah studi pustaka dengan mengedepankan teknik dokumementasi sebagai alat pengumpul data. Peneliti melakukan pelacakan berbagai referensi kepustakaan yang relevan dengan tema kajian dan menemukan lebih dari 50 literatur yang bersumber dari berbagai jurnal, buku, dan referensi lainnya yang terbit minimal 10 tahun terakhir. Berdasarkan hasil penelitian diperoleh simpulan bahwa Nasr dengan konsep esoteric-nya menempatkan prinsip unitas (Tauhid) sebagai puncak integrasi di mana antara sains dan Islam melekat erat dalam tradisi asal yang sama. Kata kunci: Unitas, integrasi sains dan Islam, Seyyed Hossein Nasr